Relationship Of Nursing Services With Patient Satisfaction BPJS Inspired - Desri Meriahta Girsang; Agung Wahyudi (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2022)
Based on the Law of the Republic of Indonesia No. 36 of 2014, Health Service is any effort or activity that is carried out in an integrated, integrated and sustainable manner to maintain and improve the health status of the community in the form of disease prevention, health improvement, disease treatment, and health restoration by the government and or the community. Health services are a sub-system of health services whose main purpose is preventive (prevention) and promotive (health improvement) services with community targets. This type of research is a quantitative research that is an analytic survey with a cross sectional design which aims to determine the relationship between nursing services and BPJS patient satisfaction inpatients at Grandmed Lubuk Pakam Hospital which was observed at the same time. The population of this study were all outpatients, determined using a total sampling of 35 people. The data were processed using the chi square test at a 95% confidence level (? = 5%). The results of this study indicate that there is no relationship between nursing service on tangible dimensions (0.321> 05), empathy (0.130> 0.05), and responsiveness (0.526> 0.05), while reliability (0.652> 0.05). assurance (0.530>0.50)). With patient satisfactio bpjs patient satisfaction is inpatient at grandmed Lubuk Pakam hospital. The conclusion in this study is that there is no relationship between nursing service end satisfaction of inpatient BPJS Patients at grandmed Lubuk Pakam hospital.